Antimicrobial resistance profiles of selected commensal bacteria isolated from impala (Aepyceros melampus) and their water sources in the Kruger National Park - Jenkins, Akinbowale Olajide (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.